Defects of metabolism of fatty acids in the sudden infant death syndrome. Issue 6484 (15th June 1985) - Howat, A J; Bennett, M J; Variend, S; Shaw, L; Engel, P C
Abstract : Two hundred consecutive cases of the sudden infant death syndrome were reviewed for the presence of fat in the liver; 14 showed diffuse panlobular microvesicular fatty change indistinguishable from that found in Reye's syndrome. Samples of frozen liver were available in five of the 14 cases; histochemical analysis showed well preserved cytochrome oxidase and succinate dehydrogenase activity in all five, uncharacteristic of Reye's syndrome. Fatty acyl-coenzyme A dehydrogenase activity in the liver was assayed biochemically in two of the same five cases with severe hepatic fatty infiltration; both showed a defect in medium chain acyl-coenzyme A dehydrogenase activity using the substrate octanoyl-coenzyme A. Both cases also showed cerebral oedema in association with fatty infiltration of renal tubules, myocardium, and skeletal muscle, characteristic of Reye's syndrome. It is concluded that diffuse panlobular microvesicular fatty change of the liver in victims of the sudden infant death syndrome, although essentially non-specific, indicates that the state of mitochondrial enzymes should be investigated.